2000
DOI: 10.1038/sj.jp.7200349
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Vibration in Neonatal Transport: A Randomized Study of Different Mattresses

Abstract: OBJECTIVE:To test the hypothesis that a gel mattress is most effective in attenuating mechanical vibration in neonatal transport, we performed a randomized block study of four mattress combinations (none, foam, gel, gel on foam) using mannequins and an ambulance traveling on fixed routes (city, highway). STUDY DESIGN:Mechanical vibration was assessed by measuring vertical accelerations at two locations: the forehead of a 2000-gm mannequin and the transport incubator base. From time histories of these accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…Compared to the incubator chassis, spectral density in the 3–20 Hz range is up to four times higher at the torso and forehead sensor sites, indicating that vibration is amplified over this spectral range. This finding is in agreement with a previous study by Gajendragadkar et al, 13 in which the mattress system amplified vibration magnitude by factors of between 2.2 to 3.4 (sponge) and 1.1 to 2.1 (gel type). However, this previous study is not directly comparable, as it compared RMS values computed from 50 Hz low-pass-filtered acceleration data.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to the incubator chassis, spectral density in the 3–20 Hz range is up to four times higher at the torso and forehead sensor sites, indicating that vibration is amplified over this spectral range. This finding is in agreement with a previous study by Gajendragadkar et al, 13 in which the mattress system amplified vibration magnitude by factors of between 2.2 to 3.4 (sponge) and 1.1 to 2.1 (gel type). However, this previous study is not directly comparable, as it compared RMS values computed from 50 Hz low-pass-filtered acceleration data.…”
Section: Resultssupporting
confidence: 93%
“…This frequency lies close to the 14 Hz chassis vibration peak, believed to originate from the engine and transmission, and so is easily excited. Mattress-induced resonance was highlighted in a previous study by Gajendragadkar et al, 13 who found vibration gain factors which are comparable to those measured in this study. However, this is the first study to demonstrate, in real patients, that the neonatal head is exposed to mechanical vibration hazard in excess of that simply observed at the incubator chassis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The accelerometer was fastened in the incubator directly under the mattress, and in theory, a vibration-dampening effect of the foam mattress on which the infant was lying cannot be excluded. However, this appears unlikely, as it has been shown that foam mattresses, like the one we used, do not attenuate vibration (14). In contrast, in adults an experimental model with constant acceleration amplitude and variable vibration frequencies showed an influence in HRV (15) and another showed that hand-transmitted vibrations lead to decreased HRV (16).…”
Section: Discussionmentioning
confidence: 69%
“…Data collection was embraced by the neonatal transport group with almost 1,700 journeys in 12 months recorded. Attaching to the neonatal trolley, along with more than 50 times the amount of data in any previous study [6], [7], [11], [12], allows a better understanding of what the baby is experiencing.…”
Section: Discussion / Impactmentioning
confidence: 99%